2015
DOI: 10.1177/003335491513000611
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Systems, and Environmental Approaches to Obesity Prevention: Translating and Disseminating Evidence from Practice

Abstract: To reduce obesity prevalence, public health practitioners are intervening to change health behaviors as well as the policies, systems, and environments (PSEs) that support healthy behaviors. Although the number of recommended PSE intervention strategies continues to grow, limited guidance is available on how to implement those strategies in practice. This article describes the University of North Carolina at Chapel Hill, Center for Training and Research Translation's (Center TRT's) approach to reviewing, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Creating an intervention database that used a typology to classify programs and projects facilitated the concept of intervention strategy count , allowing us to quantify exposure of a community to various intervention strategies implemented simultaneously by programs and projects. Our finding of a negative relationship between intervention strategy count and subsequent obesity prevalence at the ZIP Code level contributes to the mixed evidence on the impact of place-based interventions on obesity risk ( Wolfenden et al, 2014 , Leeman et al, 2015 , Boelsen-Robinson et al, 2015 , Ewart-Pierce et al, 2016 ). In another study, using this same intervention database, we showed that both macro- and micro-level intervention strategies may be important in place-based interventions ( Nianogo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Creating an intervention database that used a typology to classify programs and projects facilitated the concept of intervention strategy count , allowing us to quantify exposure of a community to various intervention strategies implemented simultaneously by programs and projects. Our finding of a negative relationship between intervention strategy count and subsequent obesity prevalence at the ZIP Code level contributes to the mixed evidence on the impact of place-based interventions on obesity risk ( Wolfenden et al, 2014 , Leeman et al, 2015 , Boelsen-Robinson et al, 2015 , Ewart-Pierce et al, 2016 ). In another study, using this same intervention database, we showed that both macro- and micro-level intervention strategies may be important in place-based interventions ( Nianogo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 50%
“…Interventions to address childhood obesity in these populations have ranged from educational programs that directly target children and/or their parents to place-based “whole-of-neighborhood interventions” that address environmental barriers to healthy eating and active living ( Egger and Swinburn, 1997 , Minkler, 1999 , Wolfenden et al, 2014 ). Over the last 1.5 decades, prominent public and private funders in this space, including the Centers for Disease Control and Prevention (CDC) and the Robert Wood Johnson Foundation, pledged more than $2 billion to reverse the obesity epidemic through place-based initiatives that emphasized policy, systems, and environmental approaches ( Leeman et al, 2015 , Centers for Disease, 2011 , Robert Wood Johnson Foundation, 2015 , Kaiser Permanente, no date , Pastor et al, 2014 ). While some of these interventions have been evaluated for outcome, to our knowledge, no published studies have examined how public and private sector resources have been distributed across geographic places to support childhood obesity interventions in communities at risk.…”
Section: Introductionmentioning
confidence: 99%
“…The Social Ecological Model highlights the complex interplay between individual, community, and societal factors that affect physical activity and nutrition behaviors and supports the creation of structure that makes healthy choices easier. While individual level prevention efforts have been shown to be minimally effective, costly, and difficult to sustain (Brownson et al, 2006), there is ever growing evidence that society, the environment, and policy have the potential to affect health behaviors (Heath et al, 2012; Hoelscher et al, 2013; Honeycutt et al, 2019; Institute of Medicine, 2011; Leeman et al, 2015). Researchers and practitioners in the fields of physical activity and nutrition have applied the Social Ecological Model and stress the importance of multiple levels of influence (Sallis et al, 2006; Story & Duffy, 2020) to support health behavior change.…”
mentioning
confidence: 99%